Use of a latex biomembrane for bladder augmentation in a rabbit model: biocompatibility, clinical and histological outcomes - Andre L. A. Domingos; Silvio Tucci Jr; Sergio B. Garcia; Jose de Bessa Jr; Adauto J. Cologna; Antonio C. P. Martins (International Brazilian Journal of Urology, 2009)
PURPOSE: To investigate histological features and biocompatibility of a latex biomembrane for bladder augmentation using a rabbit model. MATERIAL AND METHODS: After a partial cystectomy, a patch of a non-vulcanized latex biomembrane (2x4 cm) was sewn to the bladder with 5/0 monofilament polydioxanone sulfate in a watertight manner. Groups of 5 animals were sacrificed at 15, 45 and 90 days after surgery and the bladder was removed. The 5-µm preparations obtained from grafted area and normal bladder were stained with hematoxylin-eosin. Immunohistochemical staining was performed with a primary antibody against alpha-actin to assess muscle regeneration. RESULTS: No death, urinary leakage or graft extrusion occurred in any group. All bladders showed a spherical shape. Macroscopically, after 90 days, the latex biomembrane was not identifiable and the patch was indistinguishable from normal bladder. A bladder stone was found in one animal (6.6%). On the 90th day, histology revealed continuity of transitional epithelium of host bladder tissue on the patch area. At this time, the muscle layers were well organized in a similar fashion to native bladder muscle layers. The inflammatory process was higher on grafted areas when compared to controls: 15 days - p < 0.0001, 45 days - p < 0.001, and 90 days - p < 0.01. The anti alpha-actin immunoexpression peaked at 45 days, when the graft was observed covered by muscle cells. CONCLUSION: The latex biomembrane is biocompatible and can be used in models for bladder augmentation in rabbits. It promotes epithelium and muscle regeneration without urinary leakage.